Superanionic DNA: enzymatic synthesis of hypermodified DNA bearing four different anionic substituents at all four nucleobases - Kuprikova, Natalia; Ondruš, Marek; Bednárová, Lucie; Riopedre-Fernandez, Miguel; Slavětínská, Lenka Poštová; Sýkorová, Veronika; Hocek, Michal (Nucleic acids research, 2023)
We designed and synthesized a set of four 2'-deoxyribonucleoside 5'-O-triphosphates (dNTPs) derived from 5-substituted pyrimidines and 7-substituted 7-deazapurines bearing anionic substituents (carboxylate, sulfonate, phosphonate, and phosphate). The anion-linked dNTPs were used for enzymatic synthesis of modified and hypermodified DNA using KOD XL DNA polymerase containing one, two, three, or four modified nucleotides. The polymerase was able to synthesize even long sequences of >100 modified nucleotides in a row by primer extension (PEX). We also successfully combined two anionic and two hydrophobic dNTPs bearing phenyl and indole moieties. In PCR, the combinations of one or two modified dNTPs gave exponential amplification, while most of the combinations of three or four modified dNTPs gave only linear amplification in asymmetric PCR. The hypermodified ONs were successfully re-PCRed and sequenced by Sanger sequencing. Biophysical studies including hybridization, denaturation, CD spectroscopy and molecular modelling and dynamics suggest that the presence of anionic modifications in one strand decreases the stability of duplexes while still preserving the B-DNA conformation, whilst the DNA hypermodified in both strands adopts a different secondary structure.
Keywords: DNA-Directed DNA Polymerase; Base Sequence; DNA; Nucleotides; DNA-dependentní DNA-polymerasy; pyrimidiny; nukleotidy; Pyrimidines; sekvence nukleotidů